Pariwisata Petualangan Berbasis Darat di Kabupaten Karangasem - I Made Bayu Ariwangsa; Dian Pramita Sugiarti (JURNAL DESTINASI PARIWISATA, 2021)
Adventure tourism is an outdoor activity that has grown and developed in recent years and is becoming increasingly popular as a nature-based regional development model. Adventure activities, especially mountain bikes, are mostly carried out by tourists visiting Bali. Karangasem Regency has a unique geographical condition in the form of a mountainous area that strongly supports the development of mountain biking activities. By examining the potential of adventure tourism owned by Karangasem Regency, it can be seen that the supporting resources of adventure tourism in the implementation of mountain biking activities in Karangasem Regency can be identified.This research is a qualitative research with a phenomenological approach. It uses purposive sampling and snowball sampling to determine and select informants. The data were collected by using a participatory observation by trying mountain bike activities in mountain area and interview the informants. The data analysis applied the content and meaning analysis using a qualitative descriptive method. The theory used in the analysis is adventure approach theory and tourism development components.The results of the analysis reveal that the supporting resources for mountain biking activities that are not yet fully available are contained in the location criteria related to permits and regulations, so that an appropriate plan is needed in order to meet the basic criteria in the completeness of supporting resources for adventure tourism. While the criteria for activity, security, natural resources and the environment, as well as the operational sector are almost entirely available, requiring development that is in accordance to make a sustainable mountain biking activities in Karangasem Regency. Keywords: Mountain Bike Activity, Adventure Tourism, Supporting Resources Criteria.